ANALYSIS ON CIRCULAR ECONOMY AND TECHNOLOGY INNOVATION TOWARDS SUSTAINABILITY IN THE MANUFACTURING SECTOR: A BIBLIOMETRIC ANALYSIS (IITM JOURNAL OF BUSINESS STUDIES (JBS), 2024)
There has been a growing recognition of  the imperative to transition towards more  sustainable practices in the manufacturing  sector. Aiming towards sustainable practices,  the concepts of circular economy and  technological innovation offer promising  avenues for achieving sustainability goals.  In this context, the aim is to examine the  evolving research landscape concerning the  integration of circular economy principles and  technological innovation toward sustainability  in the manufacturing sector. To achieve this  objective, bibliometrics were conducted using  R-Studio. A dataset of scholarly publications  from Scopus and Web of Science was used for  bibliometrics and analyzed. To analyze the key  bibliographic data such as publication titles,  authors, publication years, journal/conference  names, keywords, abstracts, citation counts,  etc., were extracted from the Scopus and Web  of Science databases. This study, with the help  of R-Studio/Biblioshiny, summarizes the data  in the form of main information of the data,  most relevant sources, sources production over  time, word cloud, and co-occurrence network  in the form of tables and figures as well. The  findings of the study reveal a growing interest in  integrating circular economy and sustainability  with 360 documents from both databases.  The key themes identified in this study are  Sustainable Development, Performance,  Management, Sustainability, and Framework.  The main limitation of the study is that it  focuses only on two databases and suggests  future research with a more analytical and  broader dataset. This study is most relevant for  research scholars by helping them identify key  research areas to explore and for organizations  and governments as well by suggesting which  areas to focus on more.
Keywords: Circular economy; technology innovation; sustainability; manufacturing sector; bibliometric analysis